Changes in the EU Beef Market - Ewa Bąk-Filipek (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article below discusses and compares changes in the beef market, occurring in the EU, to the global market. Global beef market is going through endless changes, although direction and rate of these changes vary depending on which region the analysis applies to. In recent years Polish beef market has been slowly becoming marginalized on the internal market, mainly because of the decreasing importance of beef consumption in the balance of meat consumption. The poultry market is becoming more and more important, both on the supply and demand sides. The study also draws attention to the fact that agricultural markets, the meat market in particular, are susceptible to the cyclical fluctuations on international markets. Because of that the EU policy, as well as the policy of a given country, play a big part to the individual agricultural markets.